2016
DOI: 10.18632/oncotarget.11290
|View full text |Cite
|
Sign up to set email alerts
|

Role of mir-15a/16-1 in early B cell development in a mouse model of chronic lymphocytic leukemia

Abstract: In both human chronic lymphocytic leukemia (CLL) and the New Zealand Black (NZB) murine model of CLL, decreased levels of microRNAs miR-15a/16 play an important role in the disease. Here we investigate the effects of this microRNA on early steps of B cell development and the capacity of miR-15a-deficient hematopoietic stem cells (HSC) and B1 progenitor cells (B1P) to reproduce CLL-like phenotype both in vitro and in vivo. Our results demonstrate that both miR-15a deficient HSC and B1P cells are capable of repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Furthermore, when these quercetin-treated radioresistant B-1 cells were submitted to a multiple passage in vivo , few cells were recovered and no expansion or dissemination was observed. Corroborating to this, Underbayev et al [ 33 ] demonstrated that both miR-15a deficient HSC and B-1 cell progenitors are capable of repopulating irradiated recipients and produce higher numbers of B1 cells than sources with normal miR-15a/16 levels.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, when these quercetin-treated radioresistant B-1 cells were submitted to a multiple passage in vivo , few cells were recovered and no expansion or dissemination was observed. Corroborating to this, Underbayev et al [ 33 ] demonstrated that both miR-15a deficient HSC and B-1 cell progenitors are capable of repopulating irradiated recipients and produce higher numbers of B1 cells than sources with normal miR-15a/16 levels.…”
Section: Discussionmentioning
confidence: 95%
“…Unique miRNA signatures are differentially expressed in patients with various IgVH and ZAP-70 kinase statuses and are composed of the most frequently deregulated miRNAs in different hematological malignancies, including miR-15/16, the miR-29 family and miR-155 (13,14). Increased expression levels of miR-155 in leukemia cells are associated with a more aggressive disease phenotype in patients with CLL (20).…”
Section: Discussionmentioning
confidence: 99%
“…Structurally, miRNA are short RNA molecules measuring 19-25 nucleotides in length, processed from hairpin loop structures (pre-miRNA, 60-110 nucleotides in length), which regulate the expression of protein-coding genes via complementary binding with targeted messenger RNA (10). Previously, several chromosomal abnormalities, including 11q-, 13q-, 17p-and trisomy 12, and other molecular aberrations, including the degradation or downregulation of miRNA-15a and miRNA-16-1, and the overexpression of anti-apoptotic genes, have been identified in patients with CLL (11)(12)(13)(14). Furthermore, a unique miRNA signature was revealed to be differentially expressed in patients with various immunoglobulin heavy variable 4-38-2-like (IgVH) and ζ chain of T cell receptor associated protein kinase 70 (ZAP-70) kinase statuses, and are composed of the most frequently deregulated miRNA molecules in different hematological malignancies, including miRNA-15/16, the miRNA-29 family and miR-155 (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…They can act as oncogenic molecules or as tumor suppressors with a remarkable involvement in several B-CLL signaling pathways. They appear as crucial regulators of cellular procedures such as early B-cell development [ 45 ], cell metabolism and autophagy [ 46 , 47 ], of signaling pathways including the NFkB pathway [ 20 , 48 ], the Hedgehog (Hh) signaling pathway [ 49 ], as well as of key molecules in B-CLL such as BTK [ 50 ], TCL1A [ 51 , 52 , 53 ], BCL2 [ 54 ], TERT [ 55 ], and the heat shock proteins (HSPs) [ 56 ]. Moreover, they have an exceptional involvement in distinct parts of the BCR signaling pathway, which is abnormally activated in B-CLL, as well as, in its downstream pathways [ 57 ].…”
Section: Mirnas: Regulators Biomarkers and Potential Therapeutic mentioning
confidence: 99%